Effect of Intravenous Dexamethasone on Propofol Injection Pain: A Randomized Placebo Controlled Study (Bangladesh Journal of Otorhinolaryngology, 2020)
Background and aim of study: Pain on propofol injection (POPI) is a common problem. None of the commonly used methods completely attenuate the pain. Inflammatory response to propofol contributes to the pain. This study was conducted to compare the efficacy of dexamethasone in attenuation of pain following intravenous injection of propofol.Materials and methods: A total of 80 adult patients were scheduled in this study with either sex, ASA (American Society of Anesthesiologists) grade I and II, for routine elective surgical procedure under general anesthesia. The patients enrolled were divided randomly into two groups of 40 patients each. Group I received 0.15 mg/kg of intravenous dexamethasone in 5 ml normal saline and Group II (placebo group) received 5 ml of 0.9% intravenous normal saline, following exsanguination and occlusion of the vein of the arm. This was followed by 0.5 mg/kg of propofol intravenously.The patients were asked to report their pain during injection of propofol according to the McCririck and Hunter scale.Results: The incidence of pain experienced in dexamethasone group was 45% patients and in saline group was 70% patients (p